New evidence for the therapeutic potential of curcumin to treat nonalcoholic fatty liver disease in humans - Inzaugarat, Maria Eugenia (2017)
Introduction: The immune system acts on different metabolic tissues that are implicated in the pathogenesis of nonalcoholic fatty liver disease (NAFLD). Leptin and linoleic acid have the ability to potentially affect immune cells, whereas curcumin is a known natural polyphenol with antioxidant and anti-inflammatory properties. Aims: This study was designed to evaluate the pro-inflammatory and pro-oxidant effects of leptin and linoleic acid on immune cells from patients with NAFLD and to corroborate the modulatory effects of curcumin and its preventive properties against the progression of NAFLD using a high-fat diet (HFD)-induced NAFLD/nonalcoholic steatohepatitis mouse model. Results: The ex vivo experiments showed that linoleic acid increased the production of reactive oxygen species in monocytes and liver macrophages, whereas leptin enhanced tumor necrosis factor-α (TNF-α) production in monocytes and interferon-γ production in circulating CD4+ cells. Conversely, oral administration of curcumin prevented HFD-induced liver injury, metabolic alterations, intrahepatic CD4+ cell accumulation and the linoleic acid- and leptin- induced pro-inflammatory and pro-oxidant effects on mouse liver macrophages. Conclusion: Our findings provide new evidence for the therapeutic potential of curcumin to treat human NAFLD. However, the development of a preventive treatment targeting human circulating monocytes and liver macrophages as well as peripheral and hepatic CD4+ cells requires additional research.